Darkness and light: Absence and presence in Heidegger, Derrida, and Daoism - BURIK, Steven (Institutional Knowledge at Singapore Management University, 2019)
The light metaphor is a perpetual favorite for philosophers, both East and West. I seek to revaluate its opposite, darkness. I claim that there are good reasons to favor darkness over light, or at least to not see them as mutually incompatible or in hierarchical fashion. In recent Western philosophy, both Heidegger and Derrida argue that what the light metaphor represents, the promise of clarity and objectivity, is exactly what makes Western metaphysics problematic. In Chinese philosophy, classical Daoism offers a thinking that does not favor the light metaphor over its opposite. Daoists have the good sense to acknowledge darkness as a positive contribution to human life, at the very least on par with light. I argue that both the Western criticism of the light metaphor, and the Daoist approach to light and darkness, can be read as challenging the metaphysics of presence and providing an alternative way of thought.